Biochar amendment modulates xylem ionic constituents and ABA signaling: Its implications in enhancing water-use efficiency of maize (Zea mays L.) under reduced irrigation regimes - Heng Wan; Zhenhua Wei; Chunshuo Liu; Xin Yang; Yaosheng Wang; Fulai Liu (Journal of Integrative Agriculture, 2025)
While biochar amendment enhances plant productivity and water-use efficiency (WUE), particularly under water-limited conditions, the specific mechanisms driving these benefits remain unclear. Thus, the present study aims to elucidate the synergistic effects of biochar and reduced irrigation on maize (Zea mays L.) plants, focusing on xylem composition, root-to-shoot signaling, stomatal behavior, and WUE. Maize plants were cultivated in split-root pots filled with clay loam soil, amended by either wheat-straw biochar (WSB) or softwood biochar (SWB) at 2% (w/w). Plants received full irrigation (FI), deficit irrigation (DI), or partial root-zone drying irrigation (PRD) from the 4-leaf to the grain-filling stage. Our results revealed that the WSB amendment significantly enhanced plant water status, biomass accumulation, and WUE under reduced irrigation, particularly when combined with PRD. Although reduced irrigation inhibited photosynthesis, it enhanced WUE by modulating stomatal morphology and conductance. Biochar amendment combined with reduced irrigation significantly increased xylem K+, Ca2+, Mg2+, NO3–, Cl–, PO43–, and SO42– but decreased Na+, which in turn lowered xylem pH. Moreover, biochar amendment and especially WSB amendment further increased abscisic acid (ABA) contents in both leaf and xylem sap under reduced irrigation conditions due to changes in xylem ionic constituents and pH. The synergistic interactions between xylem components and ABA led to refined adjustments in stomatal size and density, thereby affecting stomatal conductance and ultimately improving the WUE of maize plants at different scales. The combined application of WSB and PRD can, therefore, emerge as a promising approach for improving the overall plant performance of maize plants with increased stomatal adaptations and WUE, especially under water-limited conditions.